Drug adherence to anti-tubercular treatment during COVID-19 lockdown in Haldwani block of Nainital district - Maroof, Mohd; Pamei, Gaihemlung; Bhatt, Maneesh; Awasthi, Sadhana; Bahuguna, Subhash Chandra; Singh, Pankaj (Indian Journal of Community Health, 2022)
Background: India saw one of the stringent lockdowns during the COVID-19 pandemic. In the wake of this period, the normal functioning of medical services was affected. People were reluctant to seek medical attention and notification of Tuberculosis dipped. The aim of the study was to estimate the proportion of non-adherence to anti-tubercular treatment and to identify the factors affecting the non-adherence to treatment. Methods: A retrospective community-based study was conducted among 284 tuberculosis patients. They were interviewed using a pre-designed questionnaire consisting of WHO dimensions of non-adherence and lockdown related questions. Results: The proportion of non-adherence to treatment was found to be 5.3%. Factors like chronic diseases, depression, without knowledge on how the disease is transmitted and that medication can be discontinued once the symptoms subsided, alcohol consumption, and trouble accessing medicine were found to be the determining factors in non-adherence to the treatment. Conclusions: Non-adherence to anti-tuberculosis treatment in our study was low but the various dimensions of adherence along with lockdown related factors had significant impact on it. To further minimize non-adherence during emergency like the lockdown due to COVID-19 pandemic, corrective measures must be explored and implemented.